IMPLICATIONS OF PSAK 72 IMPLEMENTATION AT PT KLM AN AGRICULTURAL TECHNOLOGY-BASED START-UP - Gunawan, Nadya; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2024)
Revenue plays a primary role in measuring a company’s financial performance, thus it needs to be accurately measured in accordance with revenue recognition principles to reflect the actual income of the company. The implication of revenue recognition that is not in accordance with the contract can result in inaccuracies in the income statement. Misassessment of revenue, whether overestimated or underestimated, holds the potential to disrupt the reliability of financial information and negatively impact decision-making. This research focuses on assessing the implementation of PSAK 72 at PT KLM, an agricultural start-up that embraces agricultural technology (agritech). Qualitative descriptive method is used to depict the data gathered through interviews and observation using PSAK 72 framework as a guideline. The research reveals that revenue recognition at PT KLM aligns with the PSAK 72 guideline, even though PT KLM faced some challenges in its implementation. These findings demonstrate the company's commitment to compliance with relevant accounting standards and accurate revenue recognition. This has positive implications for the quality of financial information generated by the company.